2021
DOI: 10.1021/acs.jafc.0c06513
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning-Mediated SERS Chip Coupled Chemometric Algorithms for Detection and Photocatalytic Degradation of Pesticides in Food

Abstract: Pesticide residues in food have been a grave concern to consumers. Herein, we have developed a dual-mode SERS chip using Cu 2 O mesoporous spheres decorated with Ag nanoparticles (MCu 2 O@Ag NPs) as both sensing and degradation/ clearing unit for rapid detection of pymetrozine and thiram pesticides in tea samples. Three kinds of chemometric algorithms were comparatively applied to analyze the collected SERS spectra of pesticides. In comparison, random frog-partial least squares achieved the best performance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Insecticides are used to kill or repel insects and are often used in agricultural settings to protect crops from destruction. SERS has been used to detect several types of insecticides in the past year such as chlorpyrifos, 159,[194][195][196][197] methyl parathion, 151,[198][199][200] endosulfan, 155,201 malathion, 155 phosmet, 156 imidacloprid, 159,167,191,[202][203][204][205][206][207] phorate, 157 carbaryl, 158,208 fipronil, 158 fenitrothion, 193 acetamiprid, 165,192,205,206,209 chlorfenapyr, 210 dichlorvos, 211,212 fenobucarb, 213 thiodicarb, 208 carbendazim, 165 profenofos, 165 methomyl, 192 pymetrozine, 160,214 clothianidin and thiamethoxam. 59,206 Recently, Sulaiman et al created a technique for the sensitive detection of the insecticide chlorpyrifos using fabricated bi-metallic nanoparticle alloys in conjunction with SERS.…”
Section: Insecticidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Insecticides are used to kill or repel insects and are often used in agricultural settings to protect crops from destruction. SERS has been used to detect several types of insecticides in the past year such as chlorpyrifos, 159,[194][195][196][197] methyl parathion, 151,[198][199][200] endosulfan, 155,201 malathion, 155 phosmet, 156 imidacloprid, 159,167,191,[202][203][204][205][206][207] phorate, 157 carbaryl, 158,208 fipronil, 158 fenitrothion, 193 acetamiprid, 165,192,205,206,209 chlorfenapyr, 210 dichlorvos, 211,212 fenobucarb, 213 thiodicarb, 208 carbendazim, 165 profenofos, 165 methomyl, 192 pymetrozine, 160,214 clothianidin and thiamethoxam. 59,206 Recently, Sulaiman et al created a technique for the sensitive detection of the insecticide chlorpyrifos using fabricated bi-metallic nanoparticle alloys in conjunction with SERS.…”
Section: Insecticidesmentioning
confidence: 99%
“…River water and apple juice 9.58 nM [203] Gold nanoparticles Imidacloprid Analyte and SERS substrate - [204] Gold-gel Parathion-methyl Analyte on SERS substrate 10 -9 M [199] Silver nanoparticles Pymetrozine Apple and cabbage 0.01 mg/L [214] Silver @ DNA/PDA-cellulose nanofiber Thiamethoxam Apple 0.003 mg/kg [59] Mesoporous copper (I) oxide @ silver nanoparticles Pymetrozine and thiram Tea 0.1 ng/g [160] Gold substrate Acetamiprid and imidacloprid Plasmon activated water 5 and 10 μg/L [205] Ag@D-TMIP Carbaryl and thiodicarb Spiked tap water - [208] Silver Gold nanostars / PDMS Methyl parathion Apple 1.946 μg/mL [198] Gold @ silver nanorods Nile blue A dye and fenobucarb pesticide Analyte on SERS substrate 1.5 × 10 −8 M (fenobucarb) [213] Articles were obtained by performing the following search on Web of Science and removing non-environmental papers: SERS + Pesticide. The table details substrate type, analyte type, the sample or sample matrix used, method LOD and the corresponding reference.…”
Section: Imidaclopridmentioning
confidence: 99%
See 1 more Smart Citation
“…SERS has been used for the detection of various pesticides. 38,39 The use of organophosphorous pesticidesparaoxon ethyl and paraoxon methyl are even banned in certain regions due to concerns regarding exposure and potential impact on non-target organisms. Hence, specic detection of the presence of pesticides in drinking and human-use water is very important so that animal and human health risks can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Pymetrozine ((E)-4,5-dihydro-6-methyl-4-(3-pyridylmethyleneamino)-1,2,4-triazin-3(2H)-one) is a pyridine azomethine compound, which has four pK a values (pK a1 = 12.90, pK a2 = 3.71, pK a3 = 1.82, and pK a4 = −3.92) controlling the relative population of deprotonated, neutral and protonated forms in solution based on the pH value. Recently, multitudinous studies have been reported on the SERS detection of pymetrozine residues, which focused on complex solid SERS substrates and dry-prepared pymetrozine samples ( Shen et al, 2021 , Xu et al, 2021 , Xu et al, 2020 ). However, few test methods are available for pymetrozine detection by samples with wet preparation, and up to now the adsorption behavior of pymetrozine on SERS substrate surface has not been studied.…”
Section: Introductionmentioning
confidence: 99%